Safety and efficacy of Biomin® DC‐C as a zootechnical feed additive for weaned piglets. (16th April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive (trade name Biomin ® DC‐C) is a blend of essential oils from oregano ( Origanum vulgare L.) and from caraway seed ( Carum carvi L.) and three individual compounds (carvacrol, methyl salicylate and l ‐menthol) encapsulated with a hydrogenated vegetable oil. The additive is intended for use in feed for weaned piglets at a minimum concentration of 75 mg/kg complete feed and a recommended maximum level of 125 mg/kg complete feed. A tolerance test in which piglets were exposed to feed containing up to an intended 1, 250 mg additive/kg complete feed showed that additive is safe for piglets at the maximum recommended level with at least a sixfold margin of safety. The active components of the additive are not genotoxic and from the available residue study, based on the detection of five marker compounds, no measurable exposure of the consumers is foreseen; consequently, the use of the additive is considered safe for consumers of animal products. The FEEDAP Panel considered that exposure to users by inhalation is unlikely; in the absence of data, the Panel cannot conclude on the effects of Biomin ® DC‐C on skin and eyes. The use of the additive in animal production is not expected to pose a risk for the terrestrial or aquatic environments. Based on the results of three efficacy studies in which positive benefits were seen, the additive has a potential to improve the growth performance of weaned piglets at a minimum application rate of 75 mg/kg complete feed.